Body Shaming Utterances in Film Series of Mother Elephant: Theo van Leeuwen’s Multimodal Study - Riska Ashar; Andi Sahtiani Jahrir; Aslan Abidin; Muhammad Tahir (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2025)
This research aims to describe the form of body shaming utterances and the impact of body shaming behavior in the Mother Elephant film series based on Multimodal theory. This research uses a qualitative descriptive research method. Data collection techniques in this research were carried out using listening and documentation techniques. The results of this research prove that there are forms of speech that contain the meaning of body shaming directly and indirectly which are expressed in several points which include character descriptions (frame position, facial expressions, dialogue, costumes, hair and make-up), music (soundtrack) or sound effects, scene descriptions (situation and conflict) ), representation of the meaning of analysis, the meaning of body shaming utterances, and the role of the combination of visual and verbal modes. On the other hand, it was found that the impact experienced by the victim due to body shaming behavior on him was described in several points which included character descriptions (frame position, facial expressions, dialogue, costumes, hair and make-up), music (soundtrack) or sound effects, scene descriptions, and meaning representations so that the impact of body shaming behavior which includes psychological and emotional impacts.